Incomplete Ulnar Variant of the Superficial Palmar Arch and Its Clinical Significance: A Case Report - S.P., SAWANT (Medical Science: Recent Advances and Applications Vol. 4, 2025)
During a routine dissection session for first-year MBBS students, we observed an anatomical variation in the right upper limb of a 70-year-old embalmed male cadaver. The superficial palmar arch was found to be incomplete, formed solely by the ulnar artery on the medial side, with no contribution from the radial artery on the lateral side. The variation was carefully photographed for documentation and future reference. No associated neuromuscular anomalies were noted in the same specimen. The deep palmar arch displayed a normal formation. The arterial pattern in the left upper limb of the cadaver was entirely normal. Understanding the variations in the vascular pattern of the hand has become increasingly important in microsurgical procedures, reconstructive hand surgeries, preoperative evaluation for radial artery harvesting in myocardial revascularisation, as well as in arterial interventions such as radial artery cannulation and the radial artery forearm flap.